Leader Communication Strategy in Implementing Digital Management (2023)
Communication is an important part of today's industrial development. Especially with the disruption creating a new picture in managing human resources digitally. This research aims to describe how a leader's strategy internalizes digital management in his organizational communication. Data collection was carried out through descriptive analysis, with data collected through the process of literature study and participant observation. The result is that in developing a leadership communication strategy, literacy and ways of working that occur in the era of disruption are needed. The communication strategy is the use of mediums, setting organizational goals and policies, analyzing and solving problems, interactive communication, and giving proportional rewards and punishments.